Epidemiology of Constipation in Elderly People in Parts of China: A Multicenter Study - Du, Xiaoshan; Liu, Shuai; Jia, Peifei; Wang, Xiaodan; Gan, Jinghuan; Hu, Wenzheng; Zhu, Han; Song, Yehua; Niu, Jianping; Ji, Yong (Frontiers in Public Health, 2022)
Abstract Purpose: To investigate the epidemiological characteristics of constipation in people aged 65 years and older in several regions of China. Patients and methods: A cross-sectional study based on a cluster sampling design was conducted in four cities of China: Tianjin, Xiamen, Cangzhou and Harbin. A total of 5222 cases (age ≥ 65 years) were recruited, and the survey was conducted via centralized and household questionnaires that included the following: basic demographic characteristics such as sex, age, education, marital status, living status and occupation; social activities; duration of sleep at night; duration of menstruation and delivery times (in females); and if the participant had constipation symptoms, the severity of constipation. Constipation was diagnosed according to the Rome IV criteria. Results: Of the 5222 participants, 919 were diagnosed with constipation. The prevalence of constipation was 17.60% in elderly people ≥65 years old. Prevalence increased with age and was significantly higher in females than males (P < 0.05). Prevalence was lower in the manual compared to the non-manual worker group, and significantly increased with decreasing duration of night sleep (P < 0.05). Older age, female sex and shorter sleep duration at night were risk factors for constipation in elderly people. Conclusion: The prevalence of constipation in the elderly people in four cities of China was 17.60%, and was significantly affected by age, sex and sleep duration at night.